The Combined Influence of Maternal Medical Conditions on the Risk of Primary Cesarean Delivery - Robert Fresch; Kendal Stephens; Emily DeFranco (American Journal of Perinatology Reports, 2024)
Background Common maternal medical comorbidities such as hypertensive disorders, diabetes, tobacco use, and extremes of maternal age, body mass index, and gestational weight gain are known individually to influence the rate of cesarean delivery. Numerous studies have estimated the risk of individual conditions on cesarean delivery.